Sustainable urban form environment and responsive design: a study of hot humid cities of Kuala Lumpur and Singapore / Dasimah Omar - Omar, Dasimah (2010)
This research is to explore the sustainable urban form: environment and responsive design: a study of hot humid cities of Kuala Lumpur and Singapore. The analysis focused on major strategies which shape current urban form and impact human activities is more important in identifying key urban form values to facilities sustainability. Perception survey on residents and visitors of both cities were carried out. Expert interviews from both study areas were also conducted. The research found that the urban form or physical form for both cities is interdependently affected by the economic, social and physical development. Human activities in both cities were influenced by physical urban form and vice versa. Planning and designing sustainable cities like Kuala Lumpur and Singapore necessitates the formulation of a series of documents and guidelines that will inform urban development and ensure the cities to remain vibrant and attractively developed as conceived. These documents are to provide guidance towards sustainability for planning of future cities in the process of globalization and desirable for local requirements. By incorporating the climate responsive design strategies can help achieve both cities' vision to be the sustainable, liveable, attractive and prosperous areas by residents, business and visitors.